DEVELOPMENT OF A METHOD FOR ASSIGNING PRIVATE LOCOMOTIVES TO TRAINS - Sannytskyi, N. M; Hermaniuk, Y. M; Sharhun, T. O (Science and Transport Progress, 2021)
Purpose. Ukraine is currently in the process of reforming the railway transportations market, which is related to the implementation of European Union Directives to its legislation. As a result of these reforms, the opening of the railway transportation market for carriers independent of Ukrzaliznytsia is envisaged. In such conditions, the problem of ensuring access of rolling stock to the receiving and departure tracks and the elimination of conflict situations with train and shunting movements of rolling stock of Ukrzaliznytsia can be solved by passing trains of independent carriers according to a tight schedule. One of the use areas of private locomotives is servicing of points of mass loading or unloading of goods. One of the tasks that arises in this case is to improve the methods of assigning private locomotives to the threads of the train schedule. Methodology. The research is performed based on the methods of organization of operational work of railways and methods of linear programming. Findings. The paper considers the problem of improving the methods of calculating the size of the working fleet of locomotives. Based on the analysis of possible conditions of interaction between Ukrzaliznytsia JSC and private carriers, it is determined that one of the possible options for using private transport companies at the stage of implementation of their services will be the service of points of mass loading or unloading of goods. In the course of the research a method of determining the number of locomotives by reducing this problem to an optimization problem of purpose was developed. An example of solving the problem of determining the required working fleet of locomotives to service the transportation of grain cargo sent to the port by shipping routes and developing schedules of their turnover is given. The number of locomotives needed to service transportations was set and the procedure for their connection to trains developed. Originality. The research improves the methods of assignment locomotives to the threads of the train schedule based on the use of linear programming methods. Practical value. The results of the work allow us to assess the needs of the working fleet of locomotives in the open market of railway transportations for independent carriers.